Large-scale Mortality of Deodar Trees by the Bark Borer, Scolytus major Stebbing (scolytidae, Coleoptera), in Kulu forest Division, Himachal Pradesh - Thapa, R. S.; Singh, Pratap (Indian Forester, 1986)
Deodar forest of Kulu Forest Division have often been the scene of bark borer, Scolytus major Stebbing, outbreaks in the past. The recent outbreak occurred in August 1980 in Jari Ban forests of Parbatti Range which killed several trees. A study of borer damage was made in September 1980 on the incidence of attack and the factors responsible for pupulation build-up of the bark borer. Preventive and remedial control measures have been given. It is suggested that proper maintenance of forest sanitation and management practices in deodar forests may avert bark borer outbreak.